Seagrasses under stress: Independent negative effects of elevated temperature and light reduction at multiple levels of organization - Alissa V. Bass; Laura J. Falkenberg; Benoit Thibodeau (Limnology and Oceanography, 2025)
Seagrasses are important foundation species, which support coastal biodiversity and provide socioeconomic benefits. However, seagrasses are threatened by anthropogenic changes, including the elevated temperature associated with marine heatwaves (MHWs) and light limitation from eutrophication or increased sedimentation. In this experiment, we exposed the seagrass Halophila ovalis to 10‐d of elevated temperature, simulating a MHW, and three light intensities to examine the impacts on multiple levels of organization, that is, growth, productivity, nitrogen cycling, and leaf microbiome. We found that both the MHW temperature and decreased light independently negatively impacted seagrass growth of new leaves, with decreased light also reducing new leaf area and rhizome elongation rate, and the occurrence of MHW temperatures increasing the rate of leaf loss. Similarly, chlorophyll concentration was altered by both stressors independently, with a common response to reduced light (increased chlorophyll concentration) significantly lower under the MHW temperature. Nitrogen assimilation rate into the leaves also decreased under both MHW temperature and reduced light availability. The leaf microbiome shifted in response to the MHW temperature and lower light, with these conditions prompting relatively more anaerobic microbes but less oxidative stress‐tolerant bacteria, and less prokaryotes performing phototrophy and (oxygenic) photoautotrophy. In conclusion, we show elevated temperature representing a MHW and light limitation can drive decreased seagrass growth, chlorophyll concentration, and cause shifts in leaf microbial functional groups, although there was little interaction between stressors. It is therefore important that good water clarity and habitat health is maintained to reduce the susceptibility of seagrasses to extreme climatic events.